Bone-like features in skate suggest a novel elasmobranch synapomorphy and deep homology of trabecular mineralization patterns. (15th January 2019) - Atake, Oghenevwogaga J.; Cooper, David M.L.; Eames, B. Frank
Graphical abstract: Abstract: Bone is a defining characteristic of the vertebrate skeleton, and while chondrichthyans (sharks, skates, and other cartilaginous fishes) are vertebrates, they are hypothesized to have lost the ability to make bone during their evolution. Multiple descriptions of a bone-like tissue in neural arches of vertebrae in various shark species (selachians), however, challenge this hypothesis. Here, we extend this argument by analyzing vertebrae of two members of the batoids (the little skate Leucoraja erinacea and Eaton's skate Bathyraja eatonii ), the sister group to selachians within elasmobranchs. Micro-CT images showed a bone-like mineralization pattern in neural arches of each skate species, and histological analyses confirmed that this bone-like tissue surrounded a cartilage core, exactly as described in sharks. Another mineralization pattern identified in skate vertebrae was distinct from the polygonal tesseral and areolar patterns that classically are associated with the chondrichthyan endoskeleton. Many regions of the vertebrae, including the neural spine and transverse processes, showed this perichondral mineralization pattern, termed here trabecular tesseral. Other than the cartilage core of the neural arch, all mineralized tissues in skate vertebrae had flattened cells surrounded by matrix with bone-like histology. Analyses of quantitative microstructural parameters revealed that, compared to rat vertebrae, the bone-like mineralization pattern in the neural arches of skate vertebrae was more similar to compact bone than trabecular bone. In contrast, the thickness of the trabecular tesseral pattern was more similar to trabecular bone than compact bone of rat vertebrae. In conclusion, a bone-like tissue in neural arches of skate vertebrae appears to be a novel elasmobranch synapomorphy. We propose that the trabecular tesseral mineralization pattern in the skate might have deep homology to the mineralization pattern utilized in trabecular bone. Statement of Significance: Mineralization patterns of skeletal tissues have not been investigated thoroughly in all vertebrate clades. Despite their designation as 'cartilaginous fish', chondrichthyans clearly evolved from ancestral vertebrates that made bone. The consensus that chondrichthyans lost the ability to make bone during their evolution, however, is challenged by reports of bone and bone-like tissues in the neural arches of vertebrae in extant sharks (selachians). Here, we provide evidence from micro-CT imaging and histological analyses to support our hypothesis that a bone-like tissue is present in the neural arches of batoids (the sister group to selachians within elasmobranchs). These results argue strongly that the neural arch bone-like tissue is a previously unknown synapomorphy of elasmobranchs. In addition to the bone-like mineralization pattern identified in the neural arches, micro-CT images also showed a novel mineralization pattern which we described as trabecular tesseral. Quantitative microstructural features shared between trabecular tesseral pattern and trabecular bone (from homologous rat vertebrae) suggest that both patterns might derive from an ancestral gene network driving trabecular mineralization (i.e., deep homology).